Women, intimate partner violence, and the law - Douglas, Heather (Interpersonal violence series, 2021)
"This book explores how women from diverse backgrounds interact with the law in response to intimate partner violence, over time. Every year, millions of women globally turn to law to help them live lives free and safe from violence. Women engage with child protection services and police. They apply for civil protection orders and family court orders to help them manage their children's contact with a violent father, and take special visa pathways to avoid deportation following separation from an abuser. Women are often compelled to interact with law, through their abuser's myriad legal applications against them. While separation may seem like a solution, it often accelerates legal engagement providing new opportunities for continued abuse. Countless women who have experienced Intimate Partner Violence are enmeshed in overlapping, complex and often inconsistent legal processes. They have both fleeting and longer-term connections with legal system actors. Their stories demonstrate how abusers harness multiple aspects of the legal process, and its actors, to continue their abuse. They highlight the regular failure of legal processes and actors to comprehend the significance of non-physical abuse. Women show how legal system actors' common expectation that separation is a single event, rather than a process, has implications for their connections with law and the outcomes they achieve. From time to time, the women in this study attained the safety and closure they sought from law, sometimes in circular and unexpected ways, but their narratives demonstrate the level of endurance, tenacity and time this often required"--